Efektivitas Teknik Forward Chaining Untuk Meningkatkan Kemampuan Menggosok Gigi Pada Anak Dengan Disabilitas Intelektual Kategori Ringan - Laililyah, Fauziatul; Rusli, Rusdi; Safitri, Jehan (Jurnal Online Psikogenesis, 2023)
Intellectual disability is a disorder during a period of development characterized by deficits in conceptual, social, and practical aspects of daily life. The forward chaining technique is a chaining method in which each activity is arranged coherently and becomes a small series by teaching the first steps to success. The study aims to investigate the effectiveness of forward chaining technique in improving the teeth-brushing ability in children with mild intellectual disability. The hypothesis is that the chaining technique with forward chaining method is effective in improving the teeth-brushing ability in children with mild intellectual disability. The research method was a quasi-experiment with one group pretest-posttest design, using the purposive sampling technique with the criteria of children with mild intellectual disability, aged 6-11 years, experiencing barriers to intellectual functions, being adaptive, and unable to brush their teeth. Data was collected using assessment, observation and interviews. The assessment test tools were the CPM and Binet tests. The instrument was an observation sheet. Data were analyzed using the Paired Sample t-Test with a result of 0.04, so the Ha was accepted. It is concluded that the forward chaining technique is effective in significantly improving the teeth-brushing ability in children with mild intellectual disability.